The problem of personal data protection in the era of digitalization - Victoria M. Piskaikina; Anton G. Monetov (Russian Studies in Law and Politics, 2025)
Background. The article examines the problem of human rights protection in the era of digitalization, namely the security and confidentiality of personal data of citizens of the Russian Federation, including biometric personal data.